Panunuring leksikal at kolokasyunal ng apat na nobela ni Lazaro Francisco. - Guillermo, Ramon G. (2013)
This study proposes some new approaches in the computer-aided analysis of lexical and discursive characteristics of some Tagalog/Pilipino/Filipino literary works. The analysis will be based on four novels by Lazaro Francisco (1898-1980) spanning the years 1929 to 1977. The results demonstrate that these methods may shed light on certain discursive-ideological aspects of texts.
Keywords: Francisco, Lazaro A; Novels -- Filipino language